Respuesta :
Answer:
(a). The final velocity of the first glider is −2.15 m/s.
(b). The final velocity of the second glider is -1.67 m/s.
Explanation:
Given that,
Mass of glider = 0.140 kg
Speed = 0.900 m/s
Mass of another glider = 0.297 kg
Speed =2 .25 m/s
Suppose, Find the magnitude of the final velocity of the first glider.
Find the magnitude of the final velocity of the second glider.
(a). We need to calculate the final velocity of the first glider
Using formula of collision
[tex]v_{1}=\dfrac{u_{1}(m_{1}-m_{2})+2m_{2}u_{2}}{m_{1}+m_{2}}[/tex]
Put the value into the formula
[tex]v_{1}=\dfrac{0.900(0.140+0.297)+2\times(-0.297)\times2.25}{0.140+0.297}[/tex]
[tex]v_{1}=-2.15\ m/s[/tex]
(b). We need to calculate the final velocity of the second glider
Using formula of collision
[tex]v_{2}=\dfrac{u_{2}(m_{2}-m_{1})+2m_{1}u_{1}}{m_{1}+m_{2}}[/tex]
Put the value into the formula
[tex]v_{1}=\dfrac{-2.25(0.297+0.140)+2\times(0.140)\times0.900}{0.140+0.297}[/tex]
[tex]v_{1}=-1.67\ m/s[/tex]
Hence, (a). The final velocity of the first glider is −2.15 m/s.
(b). The final velocity of the second glider is -1.67 m/s.
Answer with Explanation:
We are given that
Mass of glider=m=0.14 kg
Initial speed of first glider, u=0.9 m/s
m'=0.297 kg
Initial speed of second glider, u'=-2.25m/s
a.We have to find the magnitude of final velocity of 0.140 kg glider.
The collision is elastic then the final velocity of 0.140 kg glider
[tex]v=\frac{(m-m')u+2m'u'}{m+m'}[/tex]
Substitute the values
[tex]v=\frac{(0.140-0.297)\times 0.9+2\times 0.297\times (-2.25)}{0.140+0.297}=-3.38m/s[/tex]
Magnitude of final velocity of 0.140 kg glider=3.38 m/s
b.[tex]v'=\frac{u'(m'-m)+2mu}{m+m'}[/tex]
[tex]v'=\frac{-2.25(0.297-0.140)+2\times 0.140\times 0.9}{0.140+0.297}=-0.23 m/s[/tex]
Hence, the magnitude of final velocity of 0.297 kg glider=0.23 m/s